Prader‐Willi Syndrome in children: Quality of life and caregiver burden. (9th January 2021) - Meade, Christina; Martin, Ruth; McCrann, Ann; Lyons, Jacqueline; Meehan, Judith; Hoey, Hilary; Roche, Edna
Abstract: Prader‐Willi syndrome is a complex condition requiring constant care and supervision of the affected child. Aim: To evaluate quality of life and caregiver burden in children with Prader‐Willi syndrome. Methods: All children with Prader‐Willi syndrome, attending a tertiary referral centre, were invited to participate (n = 44). Quality of life was evaluated using the PedsQL questionnaire. Family impact modules and parent proxy reports evaluated the impact on the quality of life of the child and family. Additional challenges were captured using a burden questionnaire. Results: Nineteen children participated. Median age was 7.9 years (0.6–18.1 years). Majority were female (n = 14, 74%). Median age at diagnosis was 2.5 weeks (range birth–2 years 8 months). Growth hormone treatment was in place for the majority (n = 14, 74%). Increased weight and age were identified as significantly impacting on family functioning and relationships. Parents perceived increased weight and age to have a significant negative impact on their child's psychosocial health and social functioning. Caregivers of children >12 years reported an increased burden of care. Disruption to routines, restriction of social activities and psychological difficulties were reported as increasing caregiver burden. Conclusion: Prader‐Willi syndrome impacts significantly on quality of life for both the affected child and the family.